ADYGHE CHRISTIANS TODAY - BABICH, Irina (CENTRAL ASIA AND THE CAUCASUS, 2017)
The author relies on field ethnographic materials, collected in the Republic of Adygea in 2016-2017, to analyze a new and little studied religious phenomenon, i.e., the emergence of Christian communities among the Adyghes, its sources and possible repercussions for the Adyghe society. The first trends became obvious in the 1990s, when the south of Russia was flooded by Western missionaries. The interrelationship between the Adyghe Protestant and Orthodox communities is discussed; the attitude of the Adyghe Christians relating to their ethnic culture, the current state of the relations between the Muslim and Christian Adyghes in Adyghea and the specifics of the everyday life of Adyghe Christians are examined. The author provides a conclusion that the emergence of the Adyghe Christians should be discussed in the context of the spiritual crisis of traditional—Muslim and ethnic—identities and the quest for new mountaineer ideologies.